Deprivation of Kazakhstan citizenship and security, legal problems (International relations and international law Journal, 2018)
The subject of the study in this article is the problem of deprivation of citizenship as a measureto prevent terrorism and other grave harm to the vital interests of Kazakhstan because of the growingterrorist threat in the current conditions of human development. The author points out that theamendment to the Constitution of the Republic of Kazakhstan with regard to the deprivation of citizenshipby a court decision for the commission of terrorist crimes and for causing other grave harm tothe vital interests of the Republic of Kazakhstan is primarily directed at the policy of national securityimplemented by the state. The study is based on the methodology of systematic analysis of deprivation of citizenship as a measure to strengthen the fight against the terrorist threat and causing seriousharm to the vital interests of the state. The author concludes that an amendment to the Basic Law ofthe country and to national legislation on deprivation of citizenship establishes an approach that doesnot contradict the provisions of article 8, paragraph 3 (a), of the 1961 Convention on the Reductionof Statelessness. At the same time, the author points out that the existing norm of the national lawon deprivation of citizenship is authoritarian because of its vagueness and scope of definition, andalso because of the absence of legal guarantees for the family of a person deprived of citizenship.In the article the author refers to international documents and cites the example of foreign legislation interms of depriving citizenship of criminal acts, which are based on disloyalty to the state. Indicates theexisting gaps in domestic legislation, the solution of which will serve to strengthen the national securityof Kazakhstan.